2018
DOI: 10.3357/amhp.5009.2018
|View full text |Cite
|
Sign up to set email alerts
|

Color Vision Tests in Pilots’ Medical Assessments

Abstract: The discrepancy in results confirms that current color vision test protocols need to be reassessed. The CAD test could be an interesting alternative to the series of tests used to assess flight crew, but it seems more selective than current tests.Marechal M, Delbarre M, Tesson J, Lacambre C, Lefebvre H, Froussart-Maille F. Color vision tests in pilots' medical assessments. Aerosp Med Hum Perform. 2018; 89(8):737-743.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 0 publications
1
7
0
Order By: Relevance
“…The qualification for CIE 3 is a pass of FD15 that is, with some limitations (Dain SA et al 2019), consistent with the ability to recognize colour codes at a short distance. In this study, ROC analysis of FD15 found a sensitivity of 1.00 at 18.64 SN, which is consistent with the suggestion by Marechal & al. (2018) to classify CVD above 18.5 SN as dichromat.…”
Section: Colour Vision Qualitysupporting
confidence: 93%
See 3 more Smart Citations
“…The qualification for CIE 3 is a pass of FD15 that is, with some limitations (Dain SA et al 2019), consistent with the ability to recognize colour codes at a short distance. In this study, ROC analysis of FD15 found a sensitivity of 1.00 at 18.64 SN, which is consistent with the suggestion by Marechal & al. (2018) to classify CVD above 18.5 SN as dichromat.…”
Section: Colour Vision Qualitysupporting
confidence: 93%
“…In this study, ROC analysis of FD15 found a sensitivity of 1.00 at 18.64 SN, which is consistent with the suggestion by Marechal & al. (2018) to classify CVD above 18.5 SN as dichromat.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The retinal anomaloscope was not available, which is the "gold standard" of color vision screening mainly in grading the severity and differentiating the red-green types, (although it's practice is more difficult and it is not applicable in young children and the diminished cognition persons) 9,10 , accordingly color vision screening was carried out via Ishihara Pseudo Isochromatic 24 plates' book, which is from the time when designed in the last century (1917 by Ishihara was regarded as the most familiar and the most applicable color vision test globally 11 , and also could be successfully achieved by children aged 3-6 years 12 . The Ishihara plate test demonstrated a sensitivity of 0.97 and a specificity of 1.00 for the color-deficiency screening 13 and could detect people with trivial red-green color vision deficiency 14 . There is a significant difference in the incidence of preschool children with color vision deficiency concerning the ethnicity and the geographical location, being highest in the non-Hispanic white ethnicity (8% in males and about 0.4% in females) and lowest in the blacks [3][4][5][6][7][8][9][10][11][12][13][14][15] .…”
Section: Discussionmentioning
confidence: 99%